2020
DOI: 10.14295/cs.v11i0.3277
|View full text |Cite
|
Sign up to set email alerts
|

Water-retaining polymers on the early growth and quality of bushy cashew (Anacardium humile A. St. Hill) seedlings

Abstract: Bushy cashew (Anacardium humile A. St. Hill) is an endemic plant species to the Brazilian Cerrado, a region characterized by scarce and poorly distributed rainfall. The use of hydrogel, a water-retaining polymer that features massive water storage and promotes its release into the environment throughout time may be an alternative to reduce the frequency irrigation in the production of bushy cashew seedlings. This study aimed to evaluate the quality and early growth of bushy cashew seedlings as a function of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…It was previously demonstrated that deeper positioning of the hydrogel minimizes the water loss rate, benefiting seedling growth. These findings complement the study by Soares et al, 57 which observed that the increase in SD of cashew seedlings is positively influenced by an increase in the amount of hydrogel used in soil conditioning. Figure 6d presents a summary of the SD values increment measured for the seedlings cultivated under various conditioning treatments relative to the days of transplantation.…”
Section: Field Experimentssupporting
confidence: 90%
“…It was previously demonstrated that deeper positioning of the hydrogel minimizes the water loss rate, benefiting seedling growth. These findings complement the study by Soares et al, 57 which observed that the increase in SD of cashew seedlings is positively influenced by an increase in the amount of hydrogel used in soil conditioning. Figure 6d presents a summary of the SD values increment measured for the seedlings cultivated under various conditioning treatments relative to the days of transplantation.…”
Section: Field Experimentssupporting
confidence: 90%